Role of Physiotherapy In Managing Pressure Ulcers: Physiotherapists' Perspective - Rida Allauddin; Farah Iqbal; Shahida Rasheed; Abeera Wahid; Muhammad Mustafa Arif (ziauddin University, 2024)
ABSTRACT Background: Pressure ulcers, although being very common, are still a neglectedfield of study in Pakistan. They can esult in debilitating complications if not treated early and properly. Proper medical care along with prompt physiotherapy is the idealistic choice in managing pressure ulcers Objectives: Assess the awareness among doctors about the role of physiotherapyin managementof pressure ulcers. Methods: Thecrosssectional survey involved 200 doctors selected by convenience sampling from government and private hospitals of Karachi. Doctors were interviewed through a structured questionnaire and p value <0.05 was considered as significant. Results: Awareness of physiotherapy among doctors, in managing pressure ulcer patients was83.5% (n=167). "Usual practice" followed by doctors in their hospital settings, involved the application of various physical agents to enhance pressure ulcer healing such as HVPCs(high voltage pulse current) 18.0% (n=36),US (ultrasound) 28.5%(n=57) and cold laser 11.0% (n=22), Practices to prevent ulceration included health education sessions only up to 44.5% (n=89). Conclusion: Our study results showedthat there was awareness amongdoctors aboutthe role of Physiotherapy in managementof pressureulcers, but even after realizing not all the doctors were referring patients for physiotherapy. Further awareness sessionsare required for spreading more knowledge among the doctors and the patients and their jamilies to preventpressure ulceration. KEY WORDS: Awareness, Pressure Ulcers, Physiotherapy.